Interview of Ronald K. McGregor by Brian Shoemaker - McGregor, Ronald K. (Byrd Polar Research Center Archival Program, 2006)
1. Dr. Thomas Jones – p.2 2. Reverend Roy Harrisville – p.3 3. Forrest Leathers – p.4 4. Gus Morrison – p.5, 6 5. Leonard Schramm – p.5 6. Cecil Schilberg – p.8, 10 7. V.A. Dorrel – p.8 8. Lois McGregor (wife) – p. 11, 61, 68 9. Admiral “Blackjack” Reed – p.11 10. Captain Dan Gallery – p. 14, 21 11. Commodore Battle – p.15 12. President F. Roosevelt – p. 16 13. Prime Minister W. Churchill – p.16 14. Admiral P.D. Stroop – p.16, 24, 25 15. Arnie Havoo – p.17 16. Captain E.M. Morgan – p.18 17. Captain Hawkins – p.18 18. Admiral Kivette – p.19 19. ___ Scott – p.22 20. Admiral Byrd – p.22 21. Graham Rowley – p.22 22. Hap Asman – p.24 23. Ed McKeller – p.25 24. Mrs. Ruth Siple – p.25 25. Capt. Allemand – p.26 26. Capt. Roy Schultz – p.26, 44 27. Lt. Commander Lou Timberlake – p.28, 77 28. Ed Todd – p.31 29. Admiral Tyree – p.34, 43, 48, 56, 64, 77, 86, 97 30. Tom Jones – p.34, 35, 56 31. Phil Smith – p.34, 56 32. Ken Moulton – p.35 33. Bill Everett – p.38, 42, 44, 56 34. Paul Siple – p.40, 56, 64 35. Ron McGregor – p.44, 56, 59, 98 36. Lt. Dave D’Vekka – p.45, 46 37. Igor Zotikov – p. 48 38. Gordon DeQ Robin – p.56, 64 39. Baron de Gerlache – p.56, 64 40. Bert Crary – p.56 41. Paul Astapenko – p.62, 63 42. Captain Schultz – p.63, 80, 85, 89 43. Finn Ronne – p.65 44. Dusty Blades – p.67 45. Arped – p.70 46. CDR Soyat – p.71 47. Ron Koss – p.72 48. Captain James Elliott – p. 85 49. Capt. Don Bursik – p. 85 50. Admiral Reedy – p. 85, 89, 90, 93, 97 51. Admiral Strain – p. 87, 89 52. Rear Admiral Foley – p.88 53. Dick Kickerson – p. 90 54. President Kennedy – p. 92, 93 55. Jerry Brown – p. 94 56. Ed Zeller – p. 94 57. Tom Jones – p. 95 58. Max Britton – p. 98, 100, 112, 116, 118, 124 59. Max Brewer – p. 98, 123 60. Beau Buck – p. 102, 104, 109, 112, 124, 126 61. Waldo Lyon – p. 102, 118 62. Dr. Igor Zotikov – p. 104 63. Willy Weeks – p. 105, 106, 112, 124 64. Norbert Untersteiner – p. 106, 112 65. Joe Pletcher, p. 106, 109, 110 66. Fred Roots – p. 108 67. Dr. Russ Banks – p. 108 68. Jack Hunt – p. 109 69. Chester McCarty ...